Euglycemic Diabetic Ketoacidosis: A Review - Modi, Anar; Agrawal, Abhinav; Morgan, Farah (Current Diabetes Reviews, 2017)
Introduction: Diabetic ketoacidosis (DKA) is one of the most serious complications of diabetes. It is characterised by the triad of hyperglycemia (blood sugar >250 mg/dl), metabolic acidosis (arterial pH <7.3 and serum bicarbonate <18 mEq/L) and ketosis. Rarely these patients can present with blood glucose (BG) levels of less than 200 mg/dl, which is defined as euglycemic DKA. The possible etiology of euglycemic DKA includes the recent use of insulin, decreased caloric intake, heavy alcohol consumption, chronic liver disease and glycogen storage disorders. DKA in pregnancy has also been reported to present with euglycemia. The recent use of sodium glucose cotransporter 2 (SGLT2) inhibitors has shed light on another possible mechanism of euglycemic DKA. Clinicians may also be misled by the presence of pseudonormoglycemia. Conclusion: Euglycemic DKA thus poses a challenge to physicians, as patients presenting with normal BG levels in ketoacidosis may be overlooked, leading to a delay in appropriate management strategies. In this article, we review all the possible etiologies and the associated pathophysiology of patients presenting with euglycemic DKA. We also discuss the approach to diagnosis and management of such patients. Despite euglycemia, ketoacidosis in diabetic patients remains a medical emergency and must be treated in a quick and appropriate manner.
Keywords: alcohol